Socio-Economic Status of Tribal Women in Tiruvannamalai District of Tamil Nadu (British Journal of Multidisciplinary and Advanced Studies, 2023)
Since history tribal women have faced problems on basis of two aspects, first one is caste discrimination and Caste discrimination is the social evil. Caste discrimination is a social evil. Various legal measures are being implemented to eliminate caste discrimination. However, caste discrimination could not be stopped. This discrimination is still practiced in the society till today.  Second one is gender discrimination and women are not treated equally to men. Women are treated as inferior to men and they do not even get their basic rights. Their rights are denied by men. In these backgrounds the study tries to investigate historical perspectives of tribal and women and to understand socio economic status of Tribal women in Tiruvannamalai district of Tamil Nadu.